Challenges of Women Career Advancement in Knowledge-based Service Industry: Case of the Banking System in Sudan - Abdelnur, Amna (International Review of Management and Marketing, 2019)
The purpose of this study is to make an assessment of the challenges to female career advancement in a knowledge-based services industry - the banking industry. In this paper the researcher is studying the challenges facing Information Technology (IT) female workforce in their profession. Several barriers prohibit promoting female workforce skills by reducing their capacity to learn and limit their competencies in providing knowledge-based enhanced services. Specific Data on barriers of women advancement in banking system was collected from 57 females working in junior and middle IT jobs in banks in Sudan. Data was collected by means of a questionnaire using purposive sampling and was analyzed using frequencies and mean. Research findings show that knowledge-based banking sector is marked by sustained growth in its services. However, the majority of the IT senior jobs are handled by male workforce. Findings showed that the gap in the skills between the two genders contributed to preference of male worker, lack of training, male domination in knowledge-based banking sector, the demanding nature of the job, less flexible time and personal barriers. The research recommended enhancing knowledge- based services by leveraging on the skills of the female workforce by training and changing the organization culture. Keywords: Career advancement , Knowledge- based Economy, Inequality JEL Classifications: M15, D63, J31 DOI: https://doi.org/10.32479/irmm.8727